Hospice in America is a disgraceful shadow of its former self, ranging from charitable endeavor to heartless business - Carrie Alani (Palliative Medicine and Hospice Care, 2025)
I’m learning there comes a time in life – providing you are both willing and able – where you review where you’ve come. You take stock of where you’ve been.